Analisis Perbedaan Biaya Riil dengan Tarif Ina- Cbg’s dan Faktor yang Mempengaruhinya pada Pasien Appendectomy Peserta BPJS Kesehatan pada RS Syarif Hidayatullah Jakarta - Alaa ‘Ulil Haqiyah; Imas Rosidawati; R. Oke Andikarya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The Indonesian Case-Based Groups (INA-CBG’s) payment system implemented under the National Health Insurance (JKN) program often results in a discrepancy between the actual cost of healthcare services and the standardized reimbursement rates, particularly in surgical cases. This study aims to analyze the difference between real hospital costs and INA-CBG’s tariffs, as well as the influencing factors among appendectomy patients covered by BPJS Kesehatan at Syarif Hidayatullah Hospital, Jakarta. This quantitative study employed a descriptive-analytic design with a retrospective cross-sectional approach. The sample consisted of 70 appendectomy patients treated between January 2023 and February 2025, selected through total sampling. Data were collected from medical records and hospital financial records and analyzed using ANOVA. The findings revealed a significant discrepancy, with actual hospital costs consistently exceeding INA-CBG’s tariffs. Significant influencing factors included gender (p=0.040), length of stay (p=0.000), severity level (p=0.001), and class of care (p=0.000), while age showed no significant effect (p=0.458). In conclusion, the INA-CBG’s reimbursement scheme does not fully reflect the actual costs incurred in appendectomy cases, particularly among patients with extended hospital stays or severe conditions. These results are expected to inform policy evaluations and revisions of INA-CBG’s tariffs in the future.